2014
DOI: 10.3126/njog.v9i1.11182
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pap Smear Database in a Community Hospital

Abstract: Aims: This study was done to find out age wise distribution pattern, cellular abnormality and adequacy of Pap smears. Methods:A retrospective study of 4800 Pap smears based on laboratory database was done from 2008 to 2011 at Helping Hands Community Hospital in Kathmandu, Nepal. Graphical method was used for normality test and frequency analysis was done using SPSS 16.Results: Out of 4794 analysable data 4.21% had abnormal cytology, all high-grade lesions were in 51-65 age group and 0.06% were detected as carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
1
0
2
Order By: Relevance
“…In the current study the prevalence of abnormal cytology was higher (12.4%) compared with previous studies from Nepal (1.7–4.2%) . This difference might be due to variation in study methodology, study site, and device used for collection of Pap smear, as well as the highly variable sensitivity and specificity of the Pap test .…”
Section: Discussioncontrasting
confidence: 79%
“…In the current study the prevalence of abnormal cytology was higher (12.4%) compared with previous studies from Nepal (1.7–4.2%) . This difference might be due to variation in study methodology, study site, and device used for collection of Pap smear, as well as the highly variable sensitivity and specificity of the Pap test .…”
Section: Discussioncontrasting
confidence: 79%
“…In our study there were 10 cases of malignancy (0.97%) which is higher than reported by many studies. 17,19,21,23,26,27 Out of malignancies, Squamous Cell Carcinoma (80%) was found to be the most common malignancy which is in consistent with other studies. 12,17,21,23,[26][27][28] The services rendered in the hospital is free for the patients hence all women eligible for study did not deny the test due to financial problems.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, 3.6% of sample ware excluded from study due to sample inadequacy or being unsatisfactory which was lower than reported by 16,17,19,22,23 Bacterial vaginosis (1.9%) was the commonest organism isolated in our study which is same as reported by other studies done in Nepal and India. The percentage reported in these study vary from 3.3% to 7.6%.…”
Section: Discussioncontrasting
confidence: 42%